2021
DOI: 10.3389/fendo.2021.631097
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Nomogram for Predicting the Risk of Subchorionic Hematoma in Early Pregnancy With In Vitro Fertilization-Embryo Transfer/Frozen Embryo Transfer

Abstract: BackgroundSubchorionic hematoma (SCH) is common in early pregnancy achieved by in vitro fertilization-embryo transfer/frozen embryo transfer (IVF-ET/FET), and is associated with adverse obstetric outcomes. However, there are no methods known to accurately predict the occurrence of SCH.ObjectiveTo establish a nomogram prediction model for predicting the risk of SCH in early pregnancy with IVF-ET/FET and to analyze pregnancy outcomes of patients with SCH.MethodsPatients who underwent IVF-ET/FET treatment and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Our research also revealed that hydrosalpinx remained a risk factor for SCH even after tubal ligation or salpingectomy. This may be owing to the possibility that the immune inflammatory environment associated with hydrosalpinx can disrupt ovarian and endometrial functions, further affecting embryo quality and endometrial receptivity ( 3 ). It is well-known that PCOS is related to disordered endometrial receptivity, which presents as dysregulation of endometrial sex hormone receptors, increased endometrial insulin resistance, immune-inflammatory disorder, and altered uterine vascularity ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research also revealed that hydrosalpinx remained a risk factor for SCH even after tubal ligation or salpingectomy. This may be owing to the possibility that the immune inflammatory environment associated with hydrosalpinx can disrupt ovarian and endometrial functions, further affecting embryo quality and endometrial receptivity ( 3 ). It is well-known that PCOS is related to disordered endometrial receptivity, which presents as dysregulation of endometrial sex hormone receptors, increased endometrial insulin resistance, immune-inflammatory disorder, and altered uterine vascularity ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, apart from the loss of both fetuses, SCH was not associated with other pregnancy outcomes. Similarly, Yue reported that SCH had no impact on the pregnancy outcomes of IVF pregnancies, including gestational weeks, preterm birth, and neonatal birthweight ( 3 ). Ji et al ( 8 ) and Naqvi et al ( 9 ) further reported that SCH was not associated with adverse pregnancy outcomes such as stillbirth, preeclampsia, preterm labor, low birth weight, postpartum hemorrhage, and fetal distress in twin pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the American Joint Committee on Cancer (AJCC) staging system is the primary method for predicting survival outcomes in patients with mCRC[ 9 ]. However, the T stage, N stage, and M stage are the only factors for distinguishing different prognoses, and this scheme is far from satisfactory in terms of prediction accuracy[ 10 ].…”
Section: Introductionmentioning
confidence: 99%